2018
DOI: 10.29252/beat-060201
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Traumatic Spinal Cord Injury (TSCI) in the Middle-East and North-Africa (MENA) Region: A Systematic Review and Meta-Analysis

Abstract: This review shows lack of evidence about SCI in most countries of the MENA region. More epidemiological studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
2
22
0
4
Order By: Relevance
“…An epidemiological survey conducted in Canada in 2006 showed that MVCs were the main cause of SCIs, while falls became the main cause in 2009 [17,18]. Another study from seven countries in the Middle-East and North Africa (MENA) region found that MVCs are still the leading cause of SCIs, followed by falls, gunshots, violence, and sports [19]. We found that falls (both from a small and large height) and MVCs were the main causes of SCIs and occurred in nearly all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological survey conducted in Canada in 2006 showed that MVCs were the main cause of SCIs, while falls became the main cause in 2009 [17,18]. Another study from seven countries in the Middle-East and North Africa (MENA) region found that MVCs are still the leading cause of SCIs, followed by falls, gunshots, violence, and sports [19]. We found that falls (both from a small and large height) and MVCs were the main causes of SCIs and occurred in nearly all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of the modern transportation and construction industries, the incidence of SCI has increased annually ( 2 ). Patients with SCI often exhibit severe motor and sensory paralysis and have a poor prognosis, resulting in heavy familial and societal burdens ( 3 , 4 ). In previous decades, cell transplantation has become a promising therapy for a number of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a type of damage that transforms the individual's performance in permanent or temporary form (1). These alterations happen due to lack of muscular, sensory, or autonomic nervous function in the parts below lesion level (1).…”
Section: Contextmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a type of damage that transforms the individual's performance in permanent or temporary form (1). These alterations happen due to lack of muscular, sensory, or autonomic nervous function in the parts below lesion level (1). The injury may occur in spinal cord at any levels, leading to complete or proportional injuries and loss, and muscular dysfunction of one or all senses (2).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation